Jumping Exercise Restores Stretching-Induced Power Loss in Healthy Adults - Hyun Chul Jung; Nan Hee Lee; Sukho Lee (Montenegrin Sports Academy, 2018)
Th e purpose of this study was to examine the acute eff ects of jumping exercise (JE) immediately aft er diff erent stretching protocols on fl exibility and power in healthy adults. Th is study was conducted with a balanced crossover design. Th irteen healthy males (25.4±3.46 years old) voluntarily participated in this study. All participants randomly completed four trials, including three diff erent stretching protocols; 1) static stretching (SS), 2) dynamic stretching (DS), 3) proprioceptive neuromuscular facilitation stretching (PNFS), and 4) a non-stretching control (NS) followed by the JE with seven-day intervals between tests. JE was composed of three sets of fi ve tuck jumps. Flexibility was determined by the ability to perform a straight leg raise (SLR) and power by vertical jump performance (VJP). Both SLR and VJP were measured at four time points; 1) baseline, 2) post-jogging, 3) post-stretching, and 4) post-JE; 4 × 4 repeated measures analysis of variances were applied. Th ere were signifi cant interaction eff ects on SLR (F=8.935, p<.001) and VJP (F=3.965, p=.009). Th e SLR score increased in all stretching protocols except the NS protocol post-stretching and postJE. Aft er stretching, the VJP score decreased in the NS (-2.6%), SS (-3.6%), and PNFS (-4.4%) protocols but maintained a positive score for the DS (1.8%) protocol. However, the VJP score recovered to the previous value in the SS (3.2%) and PNFS (6.5%) protocols aft er the jumping exercise. Th e present study suggests that jumping exercise immediately aft er SS and PNFS protocols could be an effi cient program for restoring stretching-induced power loss in healthy adults.